2022
DOI: 10.1038/s41598-022-09650-7
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms of depression change with olfactory function

Abstract: Olfactory loss is associated with symptoms of depression. The present study, conducted on a large cohort of mostly dysosmic patients, aimed to investigate whether improvement in olfactory performance would correspond with a decrease in depression severity. In 171 participants (157 dysosmic), we assessed olfactory function and severity of depression before and after an average interval of 11 months, with many patients showing improvement in olfactory function. Separate analyses were conducted for (a) the whole … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 69 publications
(65 reference statements)
0
7
0
Order By: Relevance
“…In fact, the Bayesian factor demonstrated that the olfactory performance in all analyzed functions was indistinguishable in both groups. Although olfactory dysfunction is related to depression [ 24 , 53 , 67 , 68 ], the present findings emphasize the important role of TBI experience in causing depression.…”
Section: Discussionmentioning
confidence: 59%
“…In fact, the Bayesian factor demonstrated that the olfactory performance in all analyzed functions was indistinguishable in both groups. Although olfactory dysfunction is related to depression [ 24 , 53 , 67 , 68 ], the present findings emphasize the important role of TBI experience in causing depression.…”
Section: Discussionmentioning
confidence: 59%
“…Loss of smell and taste adversely affects quality of life by depriving those affected of several everyday pleasures and social bonds 6. People can also experience anorexia, food aversions, malnutrition, anxiety, and depression 7. All these disturbances can be greatly amplified by the onset of qualitative alterations, in particular by parosmia.…”
mentioning
confidence: 99%
“…Many studies have shown that olfactory impairment is associated with depression in human adults ( Atanasova et al, 2008 ; Croy et al, 2014 ; Kohli et al, 2016 ; Croy and Hummel, 2017 ; Taalman et al, 2017 ; Rochet et al, 2018 ; Rottstaedt et al, 2018 ; Wegener et al, 2018 ; Pabel et al, 2020 ; Qazi et al, 2020 ; Wang et al, 2020 ; Athanassi et al, 2021 ; Kim and Bae, 2022 ; Liu et al, 2022 ; Sabiniewicz et al, 2022 ). Moreover, olfactory dysfunction precedes and predicts the development of depression in older adults ( Eliyan et al, 2021 ).…”
Section: Olfaction Is Associated With Depressionmentioning
confidence: 99%